Digital Literacy Transformation: Digital Marketing Competence for Micro, Small, and Medium Enterprises (MSMEs) - Budi Santoso; Achmad Hufad; Uyu Wahyudin; Hiromu Inoue (Universitas Negeri Semarang, 2024)
The construction of the digital marketing transformation model is the result of input from several stakeholders, namely empirical condition analysis, theoretical studies, and in-depth studies of the results of the training so that the essence of digital marketing training is obtained in increasing the income of business actors. Marketing issues for business actors are the most important part of influencing the progress of a business, this is influenced by good communication skills. The digital era 4.0 encourages business people to always be adaptive to technology, especially when used as a marketing strategy for a business. Initially, small business actors were not very responsive to technological conditions, but Covid 19 had an impact on the sustainability of their businesses and only technology-adaptive business actors were still surviving. This research reveals a training model that can be used by the community or government in transforming digital marketing capabilities for small businesses. Qualitative research methods are used to uncover arguments, theoretical analysis, and empirical conditions that occur in society through interviews, documentation, and observation techniques. The results of the study show that this conceptual model can work well and is able to solve the financial problems of business actors if careful assistance is carried out involving various parties.